Dermatoscopy of the Borst-Jadassohn phenomenon in hidroacanthoma simplex, - Bruno de Castro e Souza; Maria Cláudia Alves Luce; Thais do Amaral Carneiro Cunha; Neusa Yuriko Sakai Valente (Sociedade Brasileira de Dermatologia, 2020)
Abstract The Borst-Jadassohn phenomenon is a morphological finding that consists of the presence of well-defined nests of cells located in the spiny stratum of an acanthotic epidermis. One of the neoplasms where this phenomenon is found is hidroacanthoma simplex. This neoplasm is considered the intraepidermal form of the eccrine poroma. Despite its benign nature, malignant transformations are reported. The present article reports a case of hidroacanthoma simplex and discusses the dermoscopy of this phenomenon.